Prediction of Intraoperative Blood Loss during Surgery of Brain Meningiomas - Eshkuvvatov, Gayrat; Asadullayev, Ulugbek; Yakubov, Jakhongir; Khodjimetov, Dilshod; Khasanov, Khabibullo (Asian Journal of Neurosurgery, 2024)
Background The utilization of preoperative embolization is a well-established method for reducing intraoperative blood loss during surgery of meningiomas. However, the exact indications and contraindications for this technique remain controversial.Objective The objective of this study is to determine the indications for preoperative embolization of brain meningiomas.Materials and Methods A retrospective analysis of 46 patients who underwent surgical resection of intracranial meningioma from 2020 to the end of 2022 was conducted. Preoperative magnetic resonance imaging (MRI) and computed tomography (CT) data were studied to assess their relationship with the volume of intraoperative blood loss.Results Invasive tumor growth and bone involvement (erosion, hyperostosis) were found to be the most significant factors influencing intraoperative blood loss (p = 0.001).Conclusion This study clearly demonstrates an association between preoperative imaging data and intraoperative blood loss, which may be useful in predicting massive bleeding during surgery.
Keywords: meningioma; blood loss risk factors; blood loss prognosis; embolization; bleeding